ของผสมแก๊สธรรมชาติเหลวและทอลูอีนสำหรับการทดแทนแก๊สโซลีน - ชาญกิจ จรูญเกียรติกำจร (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The octane number of blended NGL-toluene and NGL-ethanol are determined. The result indicated that the octane number of blended NGL-toluene was increased 3 units by adding toluene 10% by volume, the hydrocarbon of exhaust gas decreased by 23%, the amount of carbon monoxide and nitrogen oxide slightly alter the normal range. When ethanol was used in stead of toluene, the octane number was increased by 3.5 units, the hydrocarbon, carbon monoxide and nitrogen oxide are decreased by 28%, 34% and 30% respectively, compared with unleaded premium gasoline.